Car talk classics--the pinkwater files eaudiobook - Magliozzi, Ray (HighBridge Audio, 2011)
The hands-down highlight of many a Car Talk episode, Daniel Pinkwater is responsible for some of the all-time greatest moments of the program's storied history on public radio. Whether discussing man's best friend (but worst passenger) or searching for the perfect vehicle for those who are "horizontally challenged," Pinkwater keeps Tom and Ray in stitches, along with the show's far-flung audience. The latest time-wasting Car Talk collection features the official designation of the Pinkwater seating standard, the strange case of the motorhead boyfriend, the presentation of the first Car Talk Peace Prize, Stump the Chumps, a puzzler from the Lying Used Car Salesman series, a stirring recitation from a BMW owner's manual, a discussion of puking pooches, and more. It's four perfectly good hours of laughter and conversation.